2 - The United States and Security in Africa: The Impact of the Military Management of the International System - Campbell, Horace G. (Africa Development, 2017)
The focus of this article is to examine the dynamics influencing the militarization of US-Africa relations and their impact on security and transformation in Africa. The article attempts to illuminate the ideological, economic and social forces that influence the conception and practice of the militarization of US policy towards Africa. It examines contemporary global context – global capitalist crisis, forward planning for perpetual war and confrontation with China – which influence the thinking of a section of the US foreign policy establishment that advocates the militarization of US-Africa relations through AFRICOM. The conclusion calls on Africans to hold the line against the militarization of foreign policy and forward planning for war; Africans must define security in their own humanist terms and must build their capacity to hold their own and protect Africans’ security interests.